Complications of Skull Base Surgery - Sokoya, Mofiyinfolu; Mourad, Moustafa; Ducic, Yadranko (Seminars in Plastic Surgery, 2017)
Approaches to surgical management of skull base pathology and reconstruction of skull base defects have evolved over the past several decades. The goal, however, remains the same—to effectively address the pathology with minimal complications. In this article, the authors try to explore multiple complications of skull base surgery, discussing their incidence, natural course, and prevention. This will prove beneficial in optimal management of patients with a myriad of skull base disorders.
Keywords: skull base reconstruction; complications